Causal relationship between ankylosing spondylitis and ocular inflammatory diseases: a Mendelian randomization study - Wang, Yuxuan; Zhang, Caishun; Zhang, Qing; Jiang, Yutong; Zhang, Yuxuan; Dong, Jing (Frontiers in Genetics, 2024)
Background: Observational studies have shown an increased risk of ocular inflammatory diseases in patients with ankylosing spondylitis (AS), but the genetically predicted association remains unclear. The aim of this study was to systematically assess the causal relationship between AS and ocular inflammatory diseases.Methods: We conducted a two-sample mendelian randomization (MR) analysis to investigate the causal relationship between AS and several common ocular inflammatory diseases based on the genome-wide association study (GWAS) data and public health data. Five methods including inverse-variance weighted (IVW), MR-Egger, weighted median, weighted mode, and simple mode were employed. Sensitivity analysis were performed using MR-Egger intercept, mendelian randomization pleiotropy residual sum and outlier (MR-PRESSO), Cochran's Q test, outlier methods, leave-one-out analysis, and funnel plots.Results: The MR analysis showed a significantly increased risk of uveitis (ORIVW = 2.825, 95%CIIVW = 1.709-4.672, PIVW < 0.001), iridocyclitis (ORIVW = 3.806, 95%CIIVW = 2.809-5.157, PIVW < 0.001), scleritis (ORIVW = 1.738, 95%CIIVW = 1.190-2.539, PIVW < 0.001) and episcleritis (ORIVW = 5.113, 95%CIIVW = 2.067-12.645, PIVW = 0.004) associated with AS. But there was no correlation found between genetically predicted AS and keratitis (ORIVW = 1.041, 95%CIIVW = 0.886-1.222, PIVW = 0.628) and optic neuritis (ORIVW = 0.868, 95%CIIVW = 0.441-1.709, PIVW = 0.682).Conclusion: AS increases genetically predicted risk for uveitis, iridocyclitis, scleritis and episcleritis. No potential association of AS with keratitis and optic neuritis was found. It may provide clues for the prevention of AS complications.